2016
DOI: 10.1021/acschemneuro.6b00199
|View full text |Cite
|
Sign up to set email alerts
|

Classics in Chemical Neuroscience: Methylphenidate

Abstract: As the first drug to see widespread use for the treatment of attention deficit hyperactivity disorder (ADHD), methylphenidate was the forerunner and catalyst to the modern era of rapidly increasing diagnosis, treatment, and medication development for this condition. During its often controversial history, it has variously elucidated the importance of dopamine signaling in memory and attention, provoked concerns about pharmaceutical cognitive enhancement, driven innovation in controlled-release technologies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 144 publications
0
27
0
6
Order By: Relevance
“… Acinetobacter genus is characterized as phenol-degrading microorganisms which can use it as sole energy and carbon source [45]. Some strains of this genus are known to have a role in the biodegradation of a wide number of different pollutants, such as biphenyl and chlorinated biphenyl, amino acids (aniline), phenol, benzoate, crude oil, acetonitrile, and in the removal of phosphate or heavy metals [46, 47]. It has also been reported that certain Acinetobacter strains can utilize biphenyls including chlorinated biphenyls.…”
Section: Resultsmentioning
confidence: 99%
“… Acinetobacter genus is characterized as phenol-degrading microorganisms which can use it as sole energy and carbon source [45]. Some strains of this genus are known to have a role in the biodegradation of a wide number of different pollutants, such as biphenyl and chlorinated biphenyl, amino acids (aniline), phenol, benzoate, crude oil, acetonitrile, and in the removal of phosphate or heavy metals [46, 47]. It has also been reported that certain Acinetobacter strains can utilize biphenyls including chlorinated biphenyls.…”
Section: Resultsmentioning
confidence: 99%
“…Rather than in para position, the CF3 group was placed in ortho or in meta position on compounds 1a and 1b, respectively. In compounds 1c and 1d, an additional substituent in ortho position was introduced to the parent compound (22).…”
mentioning
confidence: 99%
“…The molecule also has two stereo-centres that generate 4 possible configurational isomers. These isomers are divided into two pairs of enantiomers, erythro (2R, 2'R, and 2S, 2'S) and threo (2R, 2'S, and 2S, 2'R) [36]. MPH is soluble in ethyl acetate, ether, etc., and insoluble in water [37].…”
Section: H Bond Acceptors and 4 Rotatable Bonds And Fully Complies Withmentioning
confidence: 99%